Design, synthesis and biological evaluation of 2-(4-phenylthiazol-2-yl) isoindoline-1, 3-dione derivatives as anti-prostate cancer agents. Issue 5 (1st March 2017) - Saravanan, K.; Elancheran, R.; Divakar, S.; Anand, S. Athavan Alias; Ramanathan, M.; Kotoky, Jibon; Lokanath, N.K.; Kabilan, S.
Graphical abstract: Abstract: The structural modification and molecular docking-based screening approaches on thiazole-based isoindolinediones were imposed to find the novel 2-(4-phenylthiazol-2-yl) isoindoline-1, 3-dione derivatives. The best fit compounds (6a-n ) were synthesized and evaluated their antiproliferative activities on the prostate cancer cell lines (PC-3 & LNCaP). Among them, the compound, 6m exhibited good activity, particularly on LNCaP (IC50  = 5.96 ± 1.6 μM), moderately active against PC-3 cell lines as compared to bicalutamide. The compound, 6m decreased the androgen-mediated transcription of ARE-mRNA in PSA, TMPRSS2, c-myc and cyclin D1 than R-bicalutamide. The compounds, 6e and6f were reconfirmed through single crystal XRD analysis. The ADME profiling of the test compounds was evaluated to find the drug-likeness and pharmacokinetic parameters. These findings may provide vital information for the development of anti-prostate cancer agents.